Use of Flow Cytometry for Quality Evaluation of Biomedical Cell Products - G. A. Trusov; A. A. Chaplenko; I. S. Semenova; E. V. Melnikova; Yu. V. Olefir (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Flow cytometry is the most common method of identification and quantitation of cell surface markers. Flow cytometry can be used for  cell counting and characterization of cell types and subtypes by  labeling cells with fluorochrome-conjugated monoclonal antibodies.  Manufacturers of human cell-based medicinal products have accumulated significant experience in flow cytometry and  developed a large number of procedures that can be validated and  included into cell products specifications. The present review  summarises the experience gained with the use of flow cytometry for characterization of human cell lines used to develop cell therapy  products. Since all biomedical cell products (BMCPs) have a cellular  component, it will be necessary to use the flow cytometry method for identification testing of BMCPs during evaluation of their quality.